2022
DOI: 10.3390/ijerph191912685
|View full text |Cite
|
Sign up to set email alerts
|

Using a Taxonomy to Systematically Identify and Describe Self-Management Interventions Components in Randomized Trials for COPD

Abstract: Self-management interventions (SMIs) may improve outcomes in Chronic Obstructive Pulmonary Disease (COPD). However, accurate comparisons of their relative effectiveness are challenging, partly due to a lack of clarity and detail regarding the intervention content being evaluated. This study systematically describes intervention components and characteristics in randomized controlled trials (RCTs) related to COPD self-management using the COMPAR-EU taxonomy as a framework, identifying components that are insuff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Regarding the reporting of interventions, we found much missing data on the exact way interventions were designed, the intensity of interventions, and how outcomes in studies were operationalized and measured. These findings are in agreement with the findings of comparable studies in COPD and obesity that were conducted within COMPAR-EU and also found gaps in the reporting of mode of delivery, intensity, location and providers involved and a huge variety in the way these variables were reported across studies [28,29]. This study showed that 20% of the SMIs were tailored, which means that the content of the intervention or the way it was delivered was adapted to the study population.…”
Section: Study Findings In the Context Of Other Researchsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding the reporting of interventions, we found much missing data on the exact way interventions were designed, the intensity of interventions, and how outcomes in studies were operationalized and measured. These findings are in agreement with the findings of comparable studies in COPD and obesity that were conducted within COMPAR-EU and also found gaps in the reporting of mode of delivery, intensity, location and providers involved and a huge variety in the way these variables were reported across studies [28,29]. This study showed that 20% of the SMIs were tailored, which means that the content of the intervention or the way it was delivered was adapted to the study population.…”
Section: Study Findings In the Context Of Other Researchsupporting
confidence: 89%
“…This study showed that 20% of the SMIs were tailored, which means that the content of the intervention or the way it was delivered was adapted to the study population. This percentage is higher than the percentage of tailored studies on SMIs in COPD and obesity, which were below 5% [28,29] and points to the fact that diabetes is generally a precursor in self-management research as compared to other chronic conditions [20]. Tailoring interventions in both design and content is a way to realize more person-centered care [24].…”
Section: Study Findings In the Context Of Other Researchmentioning
confidence: 90%
“…In terms of intervention reporting, our investigation revealed a significant absence of information regarding the precise design, intensity, and operationalization of outcomes. These findings are consistent with similar studies conducted within the COMPAR-EU initiative for chronic conditions like T2DM, COPD, and obesity, which also identified deficiencies in reporting mode of delivery, intensity, location, and provider involvement, along with significant heterogeneity in the reporting of these variables across studies [23,24].…”
Section: Research In Contextsupporting
confidence: 88%
“…To our knowledge, this is the first evidence map providing details on the characteristics of existing SMI for people living with overweight or obesity. We recently performed the description of SMIs components in RCTs for chronic obstructive pulmonary disease within “COMPAR-EU” project following the rapid reviews method proposed by Cochrane [45] . Again, self-management support techniques like education, self-monitoring and goal setting were the most frequently used.…”
Section: Discussionmentioning
confidence: 99%
“…Again, self-management support techniques like education, self-monitoring and goal setting were the most frequently used. However, outcomes considered important by patients were hardly taken into account [45] . We identified one previous evidence map that focused on describing obesity related determinants, specifically how psychological factors were associated with the development of obesity, but did not provide details of existing SMIs [46] .…”
Section: Discussionmentioning
confidence: 99%